E-007 Flow diversion for the treatment of posterior circulation aneurysms: a comparison between saccular and non-saccular aneurysms. (23rd July 2017) - Aguilar-Salinas, P; Brasiliense, L; Lima, J; Aghaebrahim, A; Sauvageau, E; Hanel, R
Abstract : Introduction: The use of flow diversion has been widely accepted to treat intracranial aneurysms located in the anterior circulation. However, flow diversion remains controversial and less optimistic for the treatment of posterior circulation aneurysms since publications have reported higher rates of adverse outcomes and mortality, especially when treating non-saccular aneurysms. The primary outcome measures were to evaluate the procedure-related mortality and the occurrence of major neurological complications during the peri-procedural period (within 30 days) and delayed neurological events (≥30 days). Secondary endpoints included the all-cause mortality rate, functional outcomes at discharge and at the last clinical follow-up as well as the rate of aneurysm occlusion at the last imaging follow-up. Methods: This is an observational retrospective study. We reviewed our database to identify patients with IAs that underwent endovascular treatment between February 2011 and December 2016. The inclusion criteria consisted of patients aged 18 or older with unruptured posterior circulation aneurysms that were treated with the Pipeline Embolization Device (PED). Patients with ruptured aneurysms were excluded. A neurological complication was defined as an ischemic stroke and/or intracranial hemorrhage. If the symptoms resolved within 7 days was considered minor and if they persisted longer than 7 days was defined as major. Results: A total of 31 patients with 34 aneurysms met inclusion criteria for the study. The mean age was 58.7±14.1 years. Sixteen patients were female (51.6%). The mean aneurysm size was 8.3±5.6 mm (range, 1.5–28). A total of 17 aneurysms were classified as saccular (group 1) and 17 as non-saccular (group 2). Major neurological complications within 30 days occurred more frequent in the group 2 in 6.3% (1/17) compared with the group 1. Also, minor neurological complications occurred in 18.8% (3/16) in the group 2 whereas in the group 1 occurred in 13.3% (2/16). Delayed major neurological complications occurred in both groups (13.3% vs 12.5%). The all-cause mortality rate was 6.5% (2/31) but none occurred within the peri-procedural period. At the last imaging follow-up, the aneurysm was occluded in 75% (12/16) in the group 1 whereas it occurred in 68.8% in the group 2. Based on the last clinical follow-up, 87.1% (24/29) of patients had a favorable outcome (mRS 0–2). Conclusion: Treatment of posterior circulation aneurysms with flow diversion is a feasible option regardless of lesion morphology, however, it should be considered after discarding other options. Disclosures: P. Aguilar-Salinas: None. L. Brasiliense: None. J. Lima: None. A. Aghaebrahim: None. E. Sauvageau: None. R. Hanel: 1; C; Microvention. 2; C; Medtronic; Stryker; Microvention; Codman. 4; C; Blockade Medical.